Segmental and age differences in the elastin network, collagen, and smooth muscle phenotype in the tunica media of the porcine aorta - Tonar, Zbyněk; Kubíková, Tereza; Prior, Claudia; Demjén, Erna; Liška, Václav; Králíčková, Milena; Witter, Kirsti (Annals of anatomy, 2015)
The porcine aorta is often used in studies on morphology, pathology, transplantation surgery, vascular and endovascular surgery, and biomechanics of the large arteries. Using quantitative histology and stereology, we estimated the area fraction of elastin, collagen, alpha-smooth muscle actin, vimentin, and desmin within the tunica media in 123 tissue samples collected from five segments (thoracic ascending aorta; aortic arch; thoracic descending aorta; suprarenal abdominal aorta; and infrarenal abdominal aorta) of porcine aortae from growing domestic pigs (n=25), ranging in age from 0 to 230 days. The descending thoracic aorta had the greatest elastin fraction, which decreased proximally toward the aortic arch as well as distally toward the abdominal aorta. Abdominal aortic segments had the highest fraction of actin, desmin, and vimentin positivity and all of these vascular smooth muscle markers were lower in the thoracic aortic segments. No quantitative differences were found when comparing the suprarenal abdominal segments with the infrarenal abdominal segments. The area fraction of actin within the media was comparable in all age groups and it was proportional to the postnatal growth. Thicker aortic segments had more elastin and collagen with fewer contractile cells. The collagen fraction decreased from ascending aorta and aortic arch toward the descending aorta. By revealing the variability of the quantitative composition of the porcine aorta, the results are suitable for planning experiments with the porcine aorta as a model, i.e. power test analyses and estimating the number of samples necessary to achieving a desirable level of precision. The complete primary morphometric data, in the form of continuous variables, are made publicly available for biomechanical modeling of site-dependent distensibility and compliance of the porcine aorta.
Keywords: kolagen; Muscle Contraction; Aging; Animals, Newborn; Actins; Collagen; Artery; Aorta; imunohistochemie; svalová kontrakce; Aorta, Abdominal; aktiny; aorta; aorta thoracica; Pig; Tunica media; novorozená zvířata; Sus scrofa; desmin; elastin; Desmin; svaly hladké cévní; Muscle, Smooth, Vascular; Swine; tunica media; Immunohistochemistry; stárnutí; zvířata; Elastin; vimentin; Tunica Media; Biomechanics; Stereology; Modeling; prasata; Aorta, Thoracic; Vimentin; aorta abdominalis; Animals